The Prognostic Impact of Tumor Location in pT3N0M0 Upper Urinary Tract Urothelial Carcinoma: A Retrospective Cohort Study - Chen, Tzu Shuang; Chen, Yen Ta; Wang, Hung Jen; Chiang, Po Hui; Yang, Wen Chou; Lee, Wei Ching; Chuang, Yao Chi; Cheng, Yuan Tso; Kang, Chih Hsiung; Lee, Wei Chia; Chen, Chien Hsu; Shen, Yuan Chi; et al. (Frontiers in Oncology, 2022)
Background We aimed to evaluate the impact of tumor location on cancer outcomes in patients with pT3N0M0 upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU) with bladder cuff excision. Materials and Methods We retrospectively reviewed 302 patients with pT3N0M0 UTUC who underwent RNU with bladder cuff excision at our institution between 2005 and 2019, including 191 renal pelvis tumors and 111 ureteral tumors. Clinicopathologic characteristics were compared between renal pelvis and ureter urothelial carcinomas. Multivariate Cox proportional hazard regression was used to assess the association between outcomes and clinical factors. Outcomes of interest included intravesical recurrence-free survival (IVRFS), local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), and cancer-specific survival (CSS), which were measured using the Kaplan–Meier curve with a log-rank test. Results A total of 302 patients underwent RNU with bladder cuff excision. During the median follow-up of 42.7 months, 70 (23.2%), 95 (31.5%), and 99 (32.8%) patients experienced intravesical recurrence, local recurrence, and distant metastasis, respectively. Seventy (23.2%) patients died from UTUC. Multivariate Cox regression analysis showed that tumor location was an independent predictor of local recurrence (HR = 2.05, p = 0.001), with borderline independent significance in intravesical recurrence (HR = 1.54, p = 0.074) and distant metastasis (HR = 1.45, p = 0.08). Kaplan–Meier analysis showed that ureter tumors had a worse 5-year local recurrence (log-rank p < 0.001) and borderline worse 5-year intravesical recurrence (log-rank p = 0.055) and 5-year distant metastasis (log-rank p = 0.073). Conclusion Ureter tumors seem to be associated with worse oncological outcomes, especially with local recurrence in UTUC. Further large and long-term studies are warranted for investigating biological differences based on tumor location.